Increasing the Attraction of Nature-Based Tourism in Senjoyo Salatiga by Embracing a Sustainable Development Framework - Paskah Gulo; Palupiningtyas, Dyah (MultiTech Publisher, 2024)
This research seeks to enhance the allure of Senjoyo Salatiga nature-based tourism by employing a sustainable development framework. The study utilizes a qualitative methodology with a case study approach. Data was gathered through a combination of direct observations, in-depth interviews, Focus Group Discussions (FGD), and analysis of relevant documents. The findings reveal that while Senjoyo Salatiga nature-based tourism boasts remarkable potential and appeal, it continues to face numerous obstacles in its growth, including inadequate infrastructure, ineffective management, the necessity for greater community engagement, risks to environmental sustainability, financial and human resource limitations, and rivalry from other tourist destinations. The proposed optimization strategies encompass upgrading eco-friendly infrastructure and support facilities, bolstering collaboration among stakeholders, building local community capacity and participation, creating innovative and sustainable tourism products and packages, implementing conservation and environmental protection principles, and encouraging responsible marketing and promotion. This study's discoveries contribute to the expansion of scientific knowledge in the domain of sustainable tourism and can function as a model for other nature-based tourism destinations in Indonesia. By embracing a sustainable development approach, Senjoyo Salatiga nature-based tourism has the potential to emerge as a paradigm for sustainable nature-based tourism development in Indonesia.